Qilian Jiechang Ning Alleviates TNBS-Induced Ulcerative Colitis in Mice and Segatella copri Outer Membrane Vesicle-Triggered Inflammation in Colon Epithelial Cells via the Caspase-1/11-GSDMD Pathways - Jinyang Hu; Junjie Niu; Shisheng Jiang; Yuhua Wu (Journal of Innate Immunity)
Introduction: Qilian Jiechang Ning (QJN), a traditional Chinese herbal formula, has demonstrated potential therapeutic effects in the treatment of ulcerative colitis (UC). This study aims to investigate the mechanism of QJN in the outer membrane vesicles (OMVs) of Segatella copri (S. copri)-induced colon epithelial cells and UC mice. Methods: Transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) were utilized to assess the morphology and size of OMVs. Inflammation markers and tight junction protein levels in HCoEpiCs induced by OMVs were monitored using ELISA and western blot. QJN was administered to intervene in HCoEpiCs treated with S. copri OMVs. Additionally, trinitrobenzene sulfonic acid (TNBS)-induced mouse models were conducted to evaluate the therapeutic effects of QJN on UC. Results: S. copri OMVs treated with QJN demonstrated a significant reduction in particle size, protein concentration, and LPS content. In HCoEpiCs, QJN effectively decreased the expression of inflammation-inducing cytokines (IL-1β, IL-18, IL-6, TNF-α) and proinflammatory proteins (GSDMD-N, NLRP3, ASC, cleaved Caspase-1, cleaved Caspase-4) triggered by S. copri OMVs, while enhancing the expression of tight junction proteins (ZO-1 and Occludin). In the UC mouse models, QJN significantly reduced the Disease Activity Index (DAI), improved colon length, lowered LPS levels, ameliorated colonic tissue damage, and inhibited Caspase-1- and Caspase-11-dependent inflammatory responses. Conclusion: QJN can alleviate S. copri-OMV-induced inflammatory response in colonic epithelial cells and reduce symptoms of UC in mouse models by modulating the Caspase-1 and Caspase-11 pathways.